The role of conserved lymphokine element 0 in induction and inhibition of interleukin-5 - Arthaningtyas, Estri (Curtin University, 2004)
The role of eosinophilia in allergic disorders indicates hIL-5 as a target of therapy. The conservation of hIL-5 proximal elements suggests they are important in controlling expression. Corticosteroids are important in the treatment of allergy, and are powerful inhibitors of IL-5 expression. Antisense oligonucleotides are new compounds that can specifically inhibit IL-5 production. This study aimed at understanding the role of conserved lymphokine element 0 (CLEO) in induction and inhibition of IL-5.The conserved proximal CLEO/TATA elements driving a luciferase reporter gene gave higher expression than a 500bp promoter in PER1 17 T-cell line. Two and three copies of IL-5 CLEO upstream of the silent IL-4 minimal promoter gave 150-200 fold increases in expression in forward orientation, but little activity in reverse orientation. Consequently, while CLEO is a powerful activator, it is not a classical enhancer. Antisense technology has also shown the dependence of IL-5 gene transcription on the de novo synthesis of the transcription factor Fra2.Inhibition of IL-5 reporter constructs by dexamethasone when induced by PMNcAMP, but not PMNCaI, provided a tool for understanding the mechanism. Deletion analysis identified CLEO as the key element of dexamethasone inhibition. Non-inhibition of IL-5 reporter constructs by dexamethasone in a Jurkat cell line, however, showed a possible intermediary factor involved in the inhibition mechanism.